Capacidades dinâmicas para superação de barreiras da economia circular : um estudo em empresas paraibanas - Lima, Irla Maria de Vasconcelos Feitosa (2023)
This research analyzes how dynamic capabilities can assist firms in reducing barriers that hinder the implementation of more circular practices. Specifically, it aims to (i) present an overview of research on barriers and dynamic capabilities in the context of CE; (ii) identify the barriers that companies face during the transition to more circular practices; (iii) identify the dynamic capabilities that companies need to make the transition from linear to circular practices; (iv) propose a conceptual framework that integrates dynamic capabilities that can help reduce barriers that hinder the implementation of more circular practices in the context of Paraiba companies; (v) refine the conceptual framework through case studies and present research propositions. The method employed for the development of the empirical study was the case study in companies operating in the State of Paraíba. The main data collection instrument was the interview that was elaborated considering the proposed conceptual framework. From the literature analysis, which was carried out through the systematic literature review method to know the theme, as well as to identify dynamic capabilities and transition barriers to CE, it was found that it is an emerging theme. Among the dynamic capabilities that were identified in the literature, 27 capabilities were identified, which after a process of grouping, categorization and abstraction, resulted in 10 categories of capabilities. Also, 65 barriers were identified, which after the same process, resulted in 12 categories. The literature review also allowed the identification of several CE practices, the most recurrent being recycling, reuse, remanufacturing, recover, eco-innovation and others. Based on this information, it was possible to develop a conceptual framework that was applied in practice with 4 companies in Paraiba (called A, B, C and D) that have circular initiatives and practices. It was found that, among the 4 companies analyzed, the one that faced the highest number of barriers was Company D. And, the Company that best managed to use dynamic capabilities and implement CE practices were Companies B and D. In a comparative analysis (cross-case), it was found that the barriers that most hindered the implementation of circular practices in the companies studied were the lack of consumer awareness, lack of knowledge and lack of R&D (called B1, B2 and B3 respectively). The dynamic capabilities that stood out the most to help overcome the barriers and implement CE practices were the following: design and innovation capabilities and absorptive capacity. From the empirical results, it was possible to refine the conceptual framework and generate 12 propositions. Finally, it is worth highlighting the contributions of this dissertation. The first contribution is derived from the integrative theoretical framework that shows difficulties/barriers that companies face when aiming to implement CE, and how they can overcome such barriers from dynamic capabilities. This framework can be used by other researchers who intend to explore the topic. A second relevant contribution is the 12 propositions generated from the empirical studies, as they can be tested in future studies through hypothesis testing. Each proposition represents a carefully crafted synthesis of the observed connections between specific variables, reflecting a deeper understanding of the underlying dynamics. These propositions act as conceptual building blocks, providing a structured framework for assessing and exploring the relationships between barriers and dynamic capabilities in diverse business contexts. Third, it can be stated that the application of the framework in practice through case studies brought relevant information to the companies studied, as the realization of the research allowed some reflections on the difficulties, they have to implement a cyclical business model, as well as how such companies can overcome these difficulties through dynamic capabilities. Thus, companies had a greater understanding of how dynamic capabilities of absorption, design and innovation and organizational capabilities are helping organizations to overcome such barriers.